(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
In this paper, an experimental system was designed and built to simulate conditions in the gas turbine blade cooling and run the experimental part. Boundary conditions are: inlet coolant air temperature is 300K with Reynolds numbers (Re=7901) .The surrounding constant hot air temperatures was (673 K).The numerical simulations were done by using software FLUENT version (14.5), in this part, it was presented the effect of using circular ribs having middle fin fitted in rectangular passage channel on fluid flow and heat transfer characteristics. Ribs used with pitch-rib height of 10, rectangular channel of (30x60 mm) cross section, 1.5 mm duct thickness and 0.5 m long. The temperature, velocity distribution contours, cooling air temperature distribution at the duct centerline, the inner wall surface temperature of the duct, and thermal performance factor are presented in this paper. it can be seen that the duct with all ribs with middle fins was the better case which leads to increase the coolant air temperature by (10.22 %) and decrease the inner wall temperature by (6.15 % ). The coolant air flow velocity seems to be accelerated and decelerated through the channel in the presence of ribs, so it was shown that the thermal performance factor along the duct is larger than 1, this is due to the fact that the ribs create turbulent conditions and increasing thermal surface area, and thus increasing heat transfer coefficient than the smooth channel.